Gastrointestinal and liver diseases and atrial fibrillation: a review of the literature. (April 2019) - Long, Michelle T.; Ko, Darae; Arnold, Lindsay M.; Trinquart, Ludovic; Sherer, Jason A.; Keppel, Sunny-Skye; Benjamin, Emelia J.; Helm, Robert H.
Atrial fibrillation (AF) is the most common arrhythmia worldwide and is associated with significant morbidity and mortality. A number of risk factors have been associated with AF, though few studies have explored the association between gastrointestinal and liver diseases and AF. Additionally, AF and treatment for AF may predispose to gastrointestinal and liver diseases. We review the current literature on the bidirectional associations between gastrointestinal and liver diseases and AF. We highlight the gaps in knowledge and areas requiring future investigation.